Development of pressurised hot water extraction (PHWE) for essential compounds from Moringa oleifera leaf extracts. (1st April 2015) - Matshediso, Phatsimo G.; Cukrowska, Ewa; Chimuka, Luke
Highlights: Pressurised hot water extraction (PHWE) system was optimised. Best condition for extraction of Moringa nutrients obtained. Results have wider applications in the use of PHWE system for medicinal plants and value additions in food. Abstract: Pressurised hot water extraction (PHWE) is a "green" technology which can be used for the extraction of essential components in Moringa oleifera leaf extracts. The behaviour of three flavonols (myricetin, quercetin and kaempferol) and total phenolic content (TPC) in Moringa leaf powder were investigated at various temperatures using PHWE. The TPC of extracts from PHWE were investigated using two indicators. These are reducing activity and the radical scavenging activity of 2, 2-diphenyl-1-picrylhydrazyl (DPPH). Flavonols content in the PHWE extracts were analysed on high performance liquid chromatography with ultra violet (HPLC-UV) detection. The concentration of kaempferol and myricetin started decreasing at 150 °C while that of quercetin remained steady with extraction temperature. Optimum extraction temperature for flavonols and DPPH radical scavenging activity was found to be 100 °C. The TPC increased with temperature until 150 °C and then decreased while the reducing activity increased.